A luta pelo acesso ao direito à saúde por meio do uso terapêutico da Cannabis Sativa no Estado da Paraíba - Coatti Neto, Tadeu (2020)
This research treats of the topic of therapeutic use of cannabis for people with neurological disorders and other pathologies. The general objective of this study is evaluated analyze the campaign for access to the human entitlement to health through the therapeutic use of cannabis in the state of Paraíba, through the movement headed by the Paraiba families that culminated in the founding of the Cannabis League, amid their achievements and difficulties. To this end, it is intended as specific objectives: to contextualize the entitlement to health as a human entitlement at the international and national ambit in order to situate health and medication policies, identifying limits and impasses to the access of these policies by the individual; to substantiate historically the use of cannabis as a therapeutic substance, the impasses in face of the prohibitionist perspective of drug policy converging to the emergence of campaign and movements for the decriminalization of drugs; and to reconstitute the process of struggle of family members for the entitlement of children and relatives with neurological pathologies to access the human entitlement to health through cannabis, since the judgment of Public Civil Action n o . 0802543-14.2014.4.05.8200, filed on July 31 from 2014, until the moment of institutionalization of this movement, giving rise to the Cannabic League in Paraíba, an entity that acts in the promotion and protection of the human entitlement to health. The research is based on a critical perspective of human entitlements, health and medication policies and the social movement for access to the therapeutic use of cannabis. Treat of a qualitative research in compliance with the hermeneutic dialectical method in order to analyze the contradictions between the affirmation and the effectiveness of the entitlement to health, from the perspective of the subjects involved in the process, using the semi-structured interview as a research resource and the thematic analyze of the contents (BARDIN, 2016). The study ends with the creation of the Cannabis League in Paraíba for the effectuation of the human entitlement to health through the therapeutic use of cannabis.